THE EMPLOYEE LIFECYCLE: OPTIMIZING EVERY TOUCHPOINT FROM HIRE TO RETIRE - Herri Setiawan Jasril; Ramon Zamora; Lukmanul Hakim (RADJA PUBLIKA, 2026)
In today's competitive talent landscape, organizations must transcend transactional HR practices to build a sustainable advantage. This article presents a comprehensive framework for optimizing the entire employee lifecycle—a holistic journey from initial attraction through post-employment alumni engagement. We deconstruct each critical stage—Attraction, Recruitment, Onboarding, Development, Retention, Separation, and Alumni Relations—to demonstrate how integrated, strategic management transforms potential failure points into moments of reinforcement. By aligning the employer brand promise with lived experience, honoring the psychological contract, and leveraging data-driven insights, companies can cultivate a highly engaged, productive, and loyal workforce. The result is a powerful virtuous cycle: a superior employee experience drives retention and innovation, which in turn fuels business performance and strengthens the employer brand, creating a resilient foundation for long-term organizational success.